THE GREEN ECONOMY: A PATH TOWARDS SUSTAINABLE DEVELOPMENT (European Journal of Economics, Finance and Business Development, 2025)
The green economy represents a transformative shift toward sustainable development by integrating environmental responsibility with economic growth and social well-being. This article examines the key benefits of the green economy across environmental, economic, and social dimensions. It highlights how renewable energy adoption, circular economy models, and green technologies contribute to reducing carbon emissions, increasing job creation, and enhancing public health. Furthermore, the discussion explores the challenges associated with green transition, including high initial investment costs, industry resistance, and policy gaps. The article underscores the importance of innovation, international cooperation, and regulatory frameworks in accelerating sustainability efforts. By addressing these challenges, the green economy offers a resilient and inclusive path toward long-term prosperity.